Urban Stormwater Controls Operations and Maintenance. (Manual of practice ;, 2022)
The effectiveness of stormwater management programs depends largely on how well and how safely stormwater control measures (SCMs) perform over time. This manual provides best practices for the continued operation of SCMs, with a target audience of designers, utility managers, and O&M staff.